1982
DOI: 10.1111/j.1471-4159.1982.tb12566.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic Proteins of Rodent Peripheral Nerve Myelin: Immunochemical Identification of the 21.5K, 18.5K, 17K, 14K, and P2 Proteins

Abstract: Proteins in peripheral nervous system and central nervous system myelin and homogenates of sciatic nerve and brain from young and adult mice and rats were characterized with affinity-purified anti-P2 and anti-myelin basic protein sera after electrophoretic transfer from sodium dodecyl sulfate-polyacrylamide gels to nitrocellulose sheets. Using this method we have identified a component of rodent peripheral nervous system myelin as P2 protein. Peripheral nervous system myelin also showed the presence of four ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…It also, contains an unusual tri-proline region [residues [99][100][101], which has been highlighted as an important structural feature similar to that contained in immunoglobulin G (IgG), and sequences homologous to cholera toxin A and B subunits [residues 102-118 and 67-77 in human MBP], which may possibly be involved in GM 1 ganglioside and GTP binding, as well as ADP ribosylation of MBP. In the PNS, four alternatively spliced forms of MBP are expressed in substantial amounts [138,139]. As has been reviewed in detail by Harauz et al [125], MBP interacts strongly with detergents and lipids, various metals and small ligands, and myelin and nonmyelin proteins that could be essential for the stability of myelin.…”
Section: C) Myelin Oligodendrocytic Basic Protein (Mobp)mentioning
confidence: 96%
“…It also, contains an unusual tri-proline region [residues [99][100][101], which has been highlighted as an important structural feature similar to that contained in immunoglobulin G (IgG), and sequences homologous to cholera toxin A and B subunits [residues 102-118 and 67-77 in human MBP], which may possibly be involved in GM 1 ganglioside and GTP binding, as well as ADP ribosylation of MBP. In the PNS, four alternatively spliced forms of MBP are expressed in substantial amounts [138,139]. As has been reviewed in detail by Harauz et al [125], MBP interacts strongly with detergents and lipids, various metals and small ligands, and myelin and nonmyelin proteins that could be essential for the stability of myelin.…”
Section: C) Myelin Oligodendrocytic Basic Protein (Mobp)mentioning
confidence: 96%
“…1A). Immunoblot studies have indicated the existence of additional minor MBPs, such as a "20-kDa" form, in mouse (Greenfield et al, 1982;Carson et al, 1983;B a n d et al, 1987; for reviews, see Campagnoni, 1988;Campagnoni and Macklin, 1988). However, these minor MBP-related peptides have not been characterized intensively.…”
mentioning
confidence: 99%
“…20,[44][45][46] But it is not the total count or size of axons stained with different methods that determines the walking tracks, but the regeneration and firing of myelinated nerve fibers that innervate the muscle. [47][48][49] Hence, for histomorphological assessment in this study, it was feasible to use polyclonal antibodies with a high-affinity for marking only intact MBP of nerve fibers [50][51][52] and to choose randomly selected sampling grids as a nonbiased stereologic technique for quantitative morphological assessment avoiding sampling errors. 53 By using this method, blobs that could represent residual, unphagocytosed myelin were minimized and only healthy myelin sheaths were stained.…”
Section: Discussionmentioning
confidence: 99%